Chinese funerary biographies : an anthology of remembered lives - Ebrey, Patricia Buckley, 1947-; Yao, Ping (Professor of history); Zhang, Cong, 1967- (University of Washington Press, 2019)
"Tens of thousands of epitaphs or funerary biographies survive from imperial China. Written to be engraved on stone and placed in a grave, they typically focus on the deceased's biographical information and exemplary words and deeds, expressing survivors' longing for the dead. Epitaphs provide glimpses of the lives of people who are not well-documented in such sources as the dynastic histories and local gazetteers: women, men who did not leave a mark politically, and children. This anthology makes available a set of funerary biographies covering nearly two thousand years of history, from the Han dynasty through the nineteenth century, selected for their potential as teaching material for courses on Chinese history, literature, and women's studies as well as world history. Funerary biographies, due to their inclusion of telling details about personal conduct, family life, local conditions, and social, cultural, and religious practices, can illustrate ways of thinking and the realities of daily life. Since most funerary biographies can be read and analyzed on multiple levels, they have the potential to stimulate discussion of topics such as the emotional tenor of family life, rituals associated with death, whether the values seen in these biographies should be called Confucian, ways to analyze women's lives from sources written by men, and how to use sources that can be assumed to be biased. These biographies will be especially effective when combined with more readily available primary sources such as official documents, religious and intellectual discourses, and anecdotal stories, promising to generate interesting discussion about literary genre, the ways historians use sources, and how writers shape their accounts"--